INDOOR ENVIRONMENT – AIR QUALITY AND THE RISKS ON HUMAN HEALTH - VASILE, Vasilica; DIMA, Alina (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Indoor environment quality is a subject of great interest among scientists worldwide, because people spend indoors the most of their time (i.e. homes, offices, vehicles, restaurants, etc.). In this time, they are exposed to the different type of pollutants such as volatile organic compounds and particulate matter, two of the most important sources of the poor indoor air and which have been associated with various adverse health effects. The aim of our experimental studies was to monitor the volatile organic compounds belonging to different chemical categories, such as aromatics, aldehydes, halogenated compounds, esters, and the particulate matter in indoor air of three residential spaces located in urban area of Bucharest, Romania. The compounds, selected based on the effect they may have on the human health, were monitored by using the equipment based on a photo-ionization detector (PID) that detects and records, in real time, the concentrations of compounds. Because the size and concentration of the particles matter are extremely important in setting their action on the occupants’ health, were monitored the concentrations of fine and coarse particles fractions, in a volume of air taken at present time intervals, using an optical particle counter. The final purpose of this monitoring activity was, on the one hand to obtain useful information on the indoor air from residential spaces, and on the other hand, for the awareness of acute necessity for action to improve the quality of our daily indoor environment.